2015
DOI: 10.15369/sujms.27.223
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Bonding Durability of Resin-based Cement to Lithium Disilicate Glass Ceramics Using Surface Modification Methods

Abstract: : The aim of the present study was undertaken to investigate the effects of several surface modi cation methods applied to lithium disilicate glass ceramics LDCs on their bonding durability with resin-based cement. The LDC specimens were sectioned using a low-speed diamond cutting machine, crystallized by heating in a furnace, and then subjected to several surface modi cation treatments such as acid etching, sandblasting, or silica coating with silane coupling agents. Then, a cylindrical titanium with a sandbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In contrast, Sato et al (43) reported that application of silane coupling agent alone on the surface of lithium disilicate was not useful due to the debonding of specimens after themocycling. The author suggested alternative method apart from using hydrofluoric acid and encouraged the use of additional treatment along with silanization such as special gas emission method and tribochemical treatment with phosphoric acid ester monomer to enhance the activation effect of silane coupling agent.…”
Section: Titanium Base Metal and Noble Metal Alloysmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, Sato et al (43) reported that application of silane coupling agent alone on the surface of lithium disilicate was not useful due to the debonding of specimens after themocycling. The author suggested alternative method apart from using hydrofluoric acid and encouraged the use of additional treatment along with silanization such as special gas emission method and tribochemical treatment with phosphoric acid ester monomer to enhance the activation effect of silane coupling agent.…”
Section: Titanium Base Metal and Noble Metal Alloysmentioning
confidence: 97%
“…Group 1: Treat with hydrofluoric acid and silane coupling agent; Group 2: Treat with silane coupling agent; Group 3: Treat with hydrofluoric acid alone. (Filho et al, 2004) (38) .................. 33 (43) ..................... 33 Table 10 Shear bond strengths of the non-modified and modified LDC specimens. In the table supplied, across a particular row, samples denoted by the same superscript letters are not significantly different (P > 0.05).…”
Section: List Of Tablesmentioning
confidence: 99%
See 2 more Smart Citations